2023
DOI: 10.3389/fchem.2023.1132025
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic asymmetric synthesis of P-stereogenic molecules

Abstract: P-chirality broadly appears in natural and synthetic functional molecules. The catalytic synthesis of organophosphorus compounds bearing P-stereogenic centers is still challenging, due to the lack of efficient catalytic systems. This review summarizes the key achievements in organocatalytic methodologies for the synthesis of P-stereogenic molecules. Different catalytic systems are emphasized for each strategy class (desymmetrization, kinetic resolution, and dynamic kinetic resolution) with examples cited to il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…[44] Strategies for several non-metal-catalyzed syntheses of nucleoside-based, P-stereogenic drugs, such as remdesivir [(S C ,S P )-74] (Scheme 12) that was used during the COVID-19 pandemic, [45] were recently summarized in a review article. [46] Scheme 10. Synthesis of diastereomerically pure α,α-diphenyl-l-prolinolsubstituted aminophosphine oxide (1R P ,3aS C )-58, and subsequent stereospecific methanolysis (DMAP = 4-(dimethylamino)pyridine).…”
Section: Synthesis By Copper Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[44] Strategies for several non-metal-catalyzed syntheses of nucleoside-based, P-stereogenic drugs, such as remdesivir [(S C ,S P )-74] (Scheme 12) that was used during the COVID-19 pandemic, [45] were recently summarized in a review article. [46] Scheme 10. Synthesis of diastereomerically pure α,α-diphenyl-l-prolinolsubstituted aminophosphine oxide (1R P ,3aS C )-58, and subsequent stereospecific methanolysis (DMAP = 4-(dimethylamino)pyridine).…”
Section: Synthesis By Copper Catalysismentioning
confidence: 99%
“…The respective catalytic reactions gave 35–40 % conversion with N , N ‐diisopropylethylamine (DIPEA) as the base and tetrahydrofuran (THF) or dimethoxyethane (DME) as the solvent [44] . Strategies for several non‐metal‐catalyzed syntheses of nucleoside‐based, P ‐stereogenic drugs, such as remdesivir [( S C , S P )‐ 74 ] (Scheme 12) that was used during the COVID‐19 pandemic, [45] were recently summarized in a review article [46] …”
Section: Transition Metal‐catalyzed Approaches Towards P‐stereogenic ...mentioning
confidence: 99%
“…Synthetic approaches to enantiopure P(V) compounds can be subdivided into five categories (Scheme 1B). [11][12][13][14][15][16] The first approach is classical resolution and/or separation of diastereomers or enantiomers by chromatography (Scheme 1B, i). [17][18][19][20][21][22][23] A second approach revolves around the use of labile chiral auxiliaries which can be displaced by sequential diastereoselective nucleophilic additions to afford enantioenriched P(V) species (Scheme 1B, ii).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [11] investigated the diffusion barrier properties of Sn-Cu joints by electrodepositing Ni, Co, amorphous Ni-W, and amorphous Co-W on a Cu substrate and found that the amorphous Co-W has the best diffusion barrier properties. Liu et al [12] found that Co-W alloys have good diffusion barrier performance and explored the possibility of replacing the commonly used Ni barrier layer in electronic packaging. To increase the solder joint quality, the diffusion barrier layer design can also indirectly obtain optimized intermetallic compounds.…”
mentioning
confidence: 99%